A qualitative exploration of the effect of visual field loss on daily life in home-dwelling stroke survivors. (July 2019) - Hazelton, Christine; Pollock, Alex; Taylor, Anne; Davis, Bridget; Walsh, Glyn; Brady, Marian C
Objective: To explore the effect of visual field loss on the daily life of community-dwelling stroke survivors. Design: A qualitative interview study. Participants: Adult stroke survivors with visual field loss of at least six months' duration. Methods: Semi-structured interviews were conducted with a non-purposive sample of 12 stroke survivors in their own homes. These were recorded, transcribed verbatim and analyzed with the framework method, using an inductive approach. Results: Two key analytical themes emerged. 'Perception, experience and knowledge' describes participant's conflicted experience of having knowledge of their impaired vision but lacking perception of that visual field loss and operating under the assumption that they were viewing an intact visual scene when engaged in activities. Inability to recognize and deal with visual difficulties, and experiencing the consequences, contributed to their fear and loss of self-confidence. 'Avoidance and adaptation' were two typologies of participant response to visual field loss. Initially, all participants consciously avoided activities. Some later adapted to vision loss using self-directed head and eye scanning techniques. Conclusions: Visual field loss has a marked impact on stroke survivors. Stroke survivors lack perception of their visual loss in everyday life, resulting in fear and loss of confidence. Activity avoidance is a common response, but in some, it is replaced by self-initiated adaptive techniques.